2013
DOI: 10.1016/j.bbagrm.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional coactivator CIITA, a functional homolog of TAF1, has kinase activity

Abstract: The Major Histocompatibility Complex (MHC) Class II Transactivator (CIITA) mediates activated immune responses and its deficiency results in the Type II Bare Lymphocyte Syndrome. CIITA is a transcriptional co-activator that regulates γ-interferon-activated transcription of MHC class I and class II genes. It is also a functional homolog of TAF1, a component of the general transcription factor complex TFIID. TAF1 and CIITA both possess intrinsic acetyltransferase (AT) activity that is required for transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…CIITA is essential in regulating MHC proteins for both Class I (Gobin, Peijnenburg, Keijsers, & van den Elsen, 1997;Martin et al, 1997) and Class II (Chang, Guerder, Hong, van Ewijk, & Flavell, 1996;Soe, Devaiah, & Singer, 2013;Steimle, Otten, Zufferey, & Mach, 1993;Steimle, Siegrist, Mottet, Lisowska-Grospierre, & Mach, 1994). Mutation of CIITA down-regulates MHC II protein presence (Steimle et al, 1993;Wong et al, 2014), and overexpressing it restores MHC II expression in Class II-depleted cells (Chang, Fontes, Peterlin, & Flavell, 1994;Steimle et al, 1993;van der Stoep et al, 2002).…”
Section: Inhibition Of Mapk-jnk Down-regulates Mhc In 5/6nx Micementioning
confidence: 99%
“…CIITA is essential in regulating MHC proteins for both Class I (Gobin, Peijnenburg, Keijsers, & van den Elsen, 1997;Martin et al, 1997) and Class II (Chang, Guerder, Hong, van Ewijk, & Flavell, 1996;Soe, Devaiah, & Singer, 2013;Steimle, Otten, Zufferey, & Mach, 1993;Steimle, Siegrist, Mottet, Lisowska-Grospierre, & Mach, 1994). Mutation of CIITA down-regulates MHC II protein presence (Steimle et al, 1993;Wong et al, 2014), and overexpressing it restores MHC II expression in Class II-depleted cells (Chang, Fontes, Peterlin, & Flavell, 1994;Steimle et al, 1993;van der Stoep et al, 2002).…”
Section: Inhibition Of Mapk-jnk Down-regulates Mhc In 5/6nx Micementioning
confidence: 99%
“…Early studies established that CIITA is a coactivator that nucleates the formation of an enhanceosome with transcription factors binding to enhancer elements in the upstream regions of the MHC genes (5, 6). In addition, more recent studies from our lab have demonstrated that it also functions as a component of the basal transcriptional machinery (79). Here we review the two distinct mechanisms by which CIITA regulates transcription of MHC class I and II genes and speculate on how these activities may be interconnected.…”
mentioning
confidence: 99%
“…CIITA does not bind to DNA directly but rather induces expression of target genes by interacting with other nuclear transcription factors including members of the RFX, NFY, and CREB families (27)(28)(29) and, more recently, has been shown to be a functional homolog of TAF1, one of the components of the general transcription factor TFIID complex (30,31). Structurally, CIITA is a member of the NLR/Caterpillar family of genes (32) and contains a multitude of regulatory domains, including an N-terminal acidic domain responsible for transactivation; a PST domain rich in proline, serine, and threonine residues that show susceptibility to phosphorylation by several different kinases; a GTP binding domain (GBD) involved in regulating self-association, nuclear localization, and promoter transactivation; and a leucine-rich region (LRR) common to all NLR/Caterpillar proteins that modulates complex formation, nuclear localization, and CIITA-mediated gene activation (28,30,33).…”
mentioning
confidence: 99%